A selected organosilicone spray adjuvant does not enhance lethal effects of a pyrethroid and carbamate insecticide on honey bees - Wernecke, Anna; Eckert, Jakob H.; Bischoff, Gabriela; Forster, Rolf; Pistorius, Jens; Odemer, Richard (Frontiers in Physiology, 2023)
As part of the agricultural landscape, non-target organisms, such as bees, may be exposed to a cocktail of agrochemicals including insecticides and spray adjuvants like organosilicone surfactants (OSS). While the risks of insecticides are evaluated extensively in their approval process, in most parts of the world however, authorization of adjuvants is performed without prior examination of the effects on bees. Nevertheless, recent laboratory studies evidence that adjuvants can have a toxicity increasing effect when mixed with insecticides. Therefore, this semi-field study aims to test whether an OSS mixed with insecticides can influence the insecticidal activity causing increased effects on bees and bee colonies under more realistic exposure conditions. To answer this question a pyrethroid (Karate Zeon) and a carbamate (Pirimor Granulat) were applied in a highly bee attractive crop (oil seed rape) during bee flight either alone or mixed with the OSS Break-Thru S 301 at field realistic application rates. The following parameters were assessed: mortality, flower visitation, population and brood development of full-sized bee colonies. Our results show that none of the above mentioned parameters was significantly affected by the insecticides alone or their combination with the adjuvant, except for a reduced flower visitation rate in both carbamate treatments (Tukey-HSD, p < 0.05). This indicates that the OSS did not increase mortality to a biologically relevant extent or any of the parameters observed on honey bees and colonies in this trial. Hence, social buffering may have played a crucial role in increasing thresholds for such environmental stressors. We confirm that the results of laboratory studies on individual bees cannot necessarily be extrapolated to the colony level and further trials with additional combinations are required for a well-founded evaluation of these substances.